Analisis Prediksi Kebangkrutan pada Perusahaan Pertambangan Batubara yang Terdaftar di Bursa Efek Indonesia - Alvia Aliviana Muslim; Sri Mintarti; Ferry Diyanti (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2018)
Based on the background of problems in predicting bankruptcy in mining companies, then the formulation of the problem in this research is whether the mining companies listed on the stock exchange of Indonesia potentially bankruptcy based on the analysis of altman method z score. Based on the analysis that has been done, it can be drawn conclusions that have been summarized in summary the results of bankrupt prediction on the method of altman z-score is not stable every year. Altogether on altman z score method, 25% are in nonbankruptcy zone, 25% are in gray zone zone and 50% are in bankruptc zone. In this study altman z score method has a suitability level of 71.42%. For companies that are in the category of bankrupt, critical or gray zone to be able to improve the company's performance to improve the state of the company. In terms of working capital, some companies have negative working capital due to the company's current lending value that is larger than the current asset value of the company. In such case the company can reduce the current debts of the company and increase the current assets value, the current debt can be reduced by paying Timely debt and also increase sales in order to generate profits that can be used to repay debt.